2015
DOI: 10.4238/2015.may.25.14
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in drug resistance of the multiple myeloma cell line RPMI8226 to doxorubicin

Abstract: ABSTRACT.We investigated the effect of autophagy on drug resistance of multiple myeloma (MM) to doxorubicin (DOX). A DOX-resistant MM cell line (RPMI8226/DOX) was developed by progressively increasing the DOX concentration gradient. The drug resistance index was determined using the MTT method. Transmission electron microscopy, anti-light chain 3-fluorescein isothiocyanate immunofluorescence, and Western blotting were used to detect autophagy of MM cells. Flow cytometry was applied to detect changes in apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Similar results are also obtained in a multiple myeloma cell line, Pan et al (37) reported that expression level of LC3-Ⅱ was higher in DOX-resistant RPMI8226/DOX cells than in DOXsensitive RPMI8226/S cells. Similarly, compared with K562 cells, there is an increased PI3K/AKT/mTOR signaling and enhanced autophagic activity in imatinibresistant human chronic myelogenous leukemia K562R cells (38).…”
Section: Discussionsupporting
confidence: 80%
“…Similar results are also obtained in a multiple myeloma cell line, Pan et al (37) reported that expression level of LC3-Ⅱ was higher in DOX-resistant RPMI8226/DOX cells than in DOXsensitive RPMI8226/S cells. Similarly, compared with K562 cells, there is an increased PI3K/AKT/mTOR signaling and enhanced autophagic activity in imatinibresistant human chronic myelogenous leukemia K562R cells (38).…”
Section: Discussionsupporting
confidence: 80%
“…Resveratrol can enhance the chemotherapeutic potential of DOX by inducing apoptosis mediated through down regulation of autophagy in breast cancer cell lines (Rai et al, 2016). Additionally, HCQ or 3-MA can partially reverse the drug resistance of myeloma RPMI8226/DOX cells by inhibition of autophagy (Pan et al, 2015). Pirarubicin is widely used in clinical chemotherapy for bladder cancer.…”
Section: Conventional Cytotoxic Drugsmentioning
confidence: 99%
“…The double sided functions of autophagy implicate its paradoxical roles in anticancer treatments, increasing or diminishing their anticancer activity. However, an increasing amount of evidence suggests that autophagy׳s pro-survival function plays a significant role in chemoresistance in a many different cancer types33, 34, 35, 36, 37, 38.…”
Section: Mechanisms Of Multidrug Resistancementioning
confidence: 99%